2020
DOI: 10.1093/fampra/cmaa140
|View full text |Cite
|
Sign up to set email alerts
|

Education of general practitioners in the use of point-of-care ultrasonography: a systematic review

Abstract: Objective To systematically review and synthesize the published literature regarding the education of general practitioners (GPs) and GPs in training (GPTs) in the use of ultrasonography. Design This systematic review was prospectively registered in PROSPERO, conducted according to the Cochrane recommendations. We combined studies identified in a previous systematic review with studies from an updated literature search using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Previous studies [ 12 , 13 ] have described how GPs achieve ultrasound proficiency through focused practical training sessions. This study confirms that focused hands-on training is considered an important educational element for GPs striving to master the technical ability to produce ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [ 12 , 13 ] have described how GPs achieve ultrasound proficiency through focused practical training sessions. This study confirms that focused hands-on training is considered an important educational element for GPs striving to master the technical ability to produce ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
“…Some medical specialties have developed POCUS guidelines and educational programme recommendations [ 1 , 8 ]. Though POCUS is also used in primary care [ 9–11 ] there is generally a lack of formal training programmes and educational recommendations for general practitioners (GPs) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings confirm that achieving and maintaining POCUS competence requires continuous use and practice. A recent review 30 described skills assessments after short training programs for GPs, but how busy GPs will be able to maintain and develop their skills over time is an area ripe for scientific investigation. Reports have emphasized visual knowledge in relation to skills development 31,32 and international recommendations for continuous training under supervision.…”
Section: Qualitativementioning
confidence: 99%
“…Another study found that resident physicians initially failed to demonstrate sufficient sensitivity in a cohort of critically-ill patients due to a high rate of missing femoral vein thrombosis (6/21, 28%) [30]. After a 2 h course in vascular POCUS, resident physicians showed substantial agreement with radiologists for the diagnosis of clinically-relevant DVT [30,47]. A meta-analysis conducted by Lee et al revealed that the initial POCUS performer and training before the study were sources of heterogeneity.…”
Section: Educationmentioning
confidence: 99%